Cyclopropanes in organic synthesis - Kulinkovich, Oleg G., 1948- (Hoboken, New Jersey : Wiley, 2015)
This is a practical guidebook about cyclopropanes that thoroughly surveys derivatives and transformations, synthetic methods, and experimental efficiency as a gateway for further research and development in the field.- Provides comprehensive lists and synthetically-oriented synopses of cyclopropane chemistry review references along with publication data on applications in the syntheses of natural and related biologically active compounds- Acts as a resource to help readers better understand cyclopropane applications for the efficient realization of synthetically important organic transformations and popular experimental procedures- Includes new developments and up-to-date information that will lead to original methodologies for complex organic synthesis- Stresses universality, flexibility, and experimental efficiency of a strategy based on preparing cyclopropane derivatives and performing ring cleavage reactions with inexpensive reagents- Focuses on the synthetic potential of cyclopropane applications, for example the synthesis of natural compounds and other target-oriented syntheses via cyclopropane intermediaries, as well on their planning by retrosynthetic analysis.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Cyclopropane; Propane; Organic compounds -- Synthesis; SCIENCE -- Chemistry -- Organic; Cyclopropane; Organic compounds -- Synthesis; Propane; Electronic books